1997
DOI: 10.1136/bmj.315.7099.13
|View full text |Cite
|
Sign up to set email alerts
|

Dietary pattern and 20 year mortality in elderly men in Finland, Italy, and the Netherlands: longitudinal cohort study

Abstract: Dietary intake of men aged 50-70 is associated with a 20 year, all cause mortality in different cultures. The healthy diet indicator is useful in evaluating the relation of mortality to dietary patterns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
296
4
10

Year Published

2000
2000
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 343 publications
(314 citation statements)
references
References 22 publications
4
296
4
10
Order By: Relevance
“…The QFFQ was completed for foods eaten over the previous 30 d. The food intake was coded according to the South African Food Composition Database System of the South African Medical Research Council and then used to calculate the nutrient and food group intakes (23)(24)(25) . Table 1 presents the components and cut-off points of the HDI (13) and the Deficiency Score/Excess Score by Thiele et al (12) , which were used in the present study. The score by Thiele et al suggested using up to thirty nutrients in a Deficiency Score to identify a preferable diet quality and using six nutrients in an Excess Score to identify a nonpreferable diet quality.…”
Section: Methodsmentioning
confidence: 99%
“…The QFFQ was completed for foods eaten over the previous 30 d. The food intake was coded according to the South African Food Composition Database System of the South African Medical Research Council and then used to calculate the nutrient and food group intakes (23)(24)(25) . Table 1 presents the components and cut-off points of the HDI (13) and the Deficiency Score/Excess Score by Thiele et al (12) , which were used in the present study. The score by Thiele et al suggested using up to thirty nutrients in a Deficiency Score to identify a preferable diet quality and using six nutrients in an Excess Score to identify a nonpreferable diet quality.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies (8)(9)(10)(11)(12)(13)(14)(15), have evaluated the effect of different dietary patterns as defined by healthy a priori scores and certain health outcomes, including total mortality (12)(13)(14)(15). Most of them have reported an inverse association between adherence to healthy dietary patterns defined a priori and overall mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Further, focusing on specific dietary components does not take into account the existence of non-nutrient bioactive substances that may impact on disease risk (Randall et al, 1990). In a practical sense, the examination of dietary patterns is important, since it may more readily enable the identification of those groups in the population at greatest risk of diet-related morbidity and mortality (Huijbregts et al, 1997).…”
Section: Introductionmentioning
confidence: 99%